DRYING OF GREEN BEAN AND OKRA UNDER SOLAR ENERGY - Doymaz, Ibrahim (ASSOC CHEMICAL ENG, 2011)
In this study, sun drying characteristics of green bean and okra were investigated. Drying experiments were conducted in Iskenderun-Hatay, Turkey. The drying study showed that the times taken for drying of green bean and okra from the initial moisture contents of 89.5% and 88.7% (w.b.) to final moisture content of around 15 +/- 0.5% (w.b.) were 60 and 100 h in open sun drying, respectively. The constant rate period is absent in drying curves. The drying process took place in the falling rate period. The drying data were fitted to thirteen thin-layer drying models. The performance of these models was investigated by comparing the determination of coefficient (R(2)), reduced chi-square (chi(2)) and root mean square error (RMSE) between the observed and predicted moisture ratios. Estimations by Approximation of diffusion (for green bean) and Midilli et al. models (for okra) were in good agreement with the experimental data obtained.
Keywords: sun drying; green bean and okra; thin-layer drying models; non-linear regression; effective diffusivity; LAYER; SLICES; VEGETABLES; MICROWAVE; KINETICS; TOMATO; MODELS; FRUITS; RICE; Chemistry; Engineering